2014
DOI: 10.1371/journal.pone.0096634
|View full text |Cite
|
Sign up to set email alerts
|

Active Commuting Throughout Adolescence and Central Fatness before Adulthood: Prospective Birth Cohort Study

Abstract: BackgroundActive commuting is a good opportunity to accumulate physical activity (PA) across the lifespan that potentially might influence central body fat. We aimed to examine the prospective associations of active commuting at 11, 15 and 18 years of age with central body fat at 18 years.MethodsParticipants were part of a large birth cohort study in Pelotas, Brazil (n = 3,649 participants). Active commuting, leisure-time PA and income were self-reported at 11, 15 and 18 years. Waist circumference and trunk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
3
6
0
Order By: Relevance
“…In the analyses of the present study, after adjusting for a series of variables known to impact the development of BF, only the vigorous-intensity physical activities among boys were inversely associated with FM at 18 years old. These findings match two other studies with similar methodologies as this one [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the analyses of the present study, after adjusting for a series of variables known to impact the development of BF, only the vigorous-intensity physical activities among boys were inversely associated with FM at 18 years old. These findings match two other studies with similar methodologies as this one [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that active travel showed substantial tracking, with 38.5% of males and 32.3% of females choosing active modes of travel at every age and the odds of maintaining active travel were increased for those who chose active modes of travel at age 12. These findings are similar to those in a recent study in Brazilian adolescents, which found substantial evidence of tracking of active travel from ages 11 to 18 years ( Martinez-Gomez et al, 2014 ). Walking demonstrated the most substantial positive tracking of all travel behaviours, while weak tracking coefficients for passive travel behaviours such as car travel were observed.…”
Section: Discussionsupporting
confidence: 91%
“…Adoption or maintenance of cycling to school by European adolescents has been shown to be associated with improved cardiorespiratory fitness ( Chillón et al, 2012 , Cooper et al, 2008 ) and cardiovascular risk profiles ( Andersen et al, 2011 ). A longitudinal study in 6–8 year old children in Canada found that sustained active travel was associated with a more healthy BMI trajectory across the early school years ( Pabayo et al, 2010 ), whilst in Brazil, both cross-sectional and prospective associations between active travel (walking/cycling) and central body fat were observed in males only ( Martinez-Gomez et al, 2014 ). Similarly, in the current study the association between active travel and BMI SDS was observed in the males only.…”
Section: Discussionmentioning
confidence: 99%
“…12,32,33,37,38 Moreover, it may be necessary to maintain the habit of ACS over time to improve the adiposity of children. 39 In the same way, our data suggest that walking to school was not associated with CRF levels in children. A systematic review that analyzed the impact of ACS on CRF found that children who bicycled to school showed higher values of CRF when compared to passive commuters, whereas the evidence for this is inconclusive for those walking to school.…”
Section: Association Between Active Commuting To School and Adipositysupporting
confidence: 62%
“…It is not surprising, therefore, that in countries where cycling is more common, ACS is associated with less adiposity . Moreover, it may be necessary to maintain the habit of ACS over time to improve the adiposity of children …”
Section: Discussionmentioning
confidence: 99%